Strategic Approaches to Improving Service Quality at Hospital - Prayoga, Alfian; Silitonga, Mala Sondang (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to formulate strategic recommendations for enhancing the service quality of RSUD Ciawi. Despite its strategic location and status as a primary referral center in Bogor Regency, RSUD Ciawi faces critical internal challenges, evidenced by low compliance rates with several National Quality Indicators (INM) (Permenkes No. 30/2022) and persistent public complaints regarding service responsiveness and reliability. This research employs a qualitative descriptive case study method utilizing SWOT analysis (Input, Matching, and Decision stages) and the SERVQUAL model dimensions (Tangibles, Reliability, Responsiveness, Assurance, and Empathy) to identify influencing factors and define actionable strategies. Key data were collected through interviews with key informants and document analysis. The findings reveal a critical lack of staff compliance in crucial clinical protocols, notably Hand Hygiene (53%–69% compliance), Use of Personal Protective Equipment (APD) (65%–81%), and Adherence to Clinical Pathways (25%–49%). Systemic weaknesses also include complicated administrative processes for emergency procedures (C-Section) and capacity limitations (inpatient beds). The resultant strategy focuses on integrated digitalization (RME/Clinical Pathway), strict disciplinary enforcement, and simplification of emergency service procedures to mitigate financial and reputational risks.